A simplified method for determining of critical swimming velocity as a swimming fatigue index for freestyle sprinters and distance swimmers - Takahashi, S.; Wakayoshi, K.; Nagasawa, S.; Sakaguchi, Y.; Kitagawa, K. (Biomechanics and Medicine in Swimming IX, 2003)
INTRODUCTION and PURPOSE: Critical swimming velocity (Vcri) is recognized to be the swimming speed corresponding to the maximal lactate steady state, and is expressed as the slope of a regression line between swimming distances and their sustained times. In a previous study, we investigated a simpler method to determine Vcri for freestyle sprinters and distance swimmers. As a result, both sprinters and distance swimmers showed significant relationships between Vcri and the swimming velocity for a distance of 300 m at maximal effort (V300), and the Vcri of sprinters and distance swimmers corresponded to the swimming velocities of 88.8 % and 91.3 % (V300). These results suggested that V300 was an appropriate swimming velocity as an endurance index from the shortest swimming distance to estimate Vcri. Therefore, the purpose of this study was to confirm that Vcri estimated by V300 shows the maximal lactate steady state. METHODS: Eight sprinters (50 m and 100 m freestyle) and eight distance swimmers (400 m and 1500 m freestyle) participated in this study, covering distances of 300 m and 2000 m at maximal effort in a 25-m swimming pool. Moreover, in the maximal lactate steady state test, the subjects were instructed to swim 2500 m(5 x 500 m) freestyle at three constant velocities (98.0 %, 100 %, 102 % of Vcri) interrupted by three short rest periods from 30 to 45 s used for blood sampling. RESULTS: Both sprinters and distance swimmers showed significant relationships between the swimming velocity for a distance of 2000 m and Vcri estimated by V300. In the maximal lactate steady state test, 100 % of Vcri showed a higher steady state than 98 % of Vcri, but 102 % of Vcri did not show the steady state for sprinters and distance swimmers. In conclusion, one timed 300 m maximal effort swimming test is believed to be a simpler, more rational method to determine Vcri for both sprinters and distance swimmers.